Diseño y simulación de un sistema automatizado para un banco de prueba de ensayo a torsión (2022)
The Antonio Nariño University has a torsion testing machine available, it has a programmable automaton for the automated operation of the equipment, however, this is not programmed according to the needs of the test and lacks the means to display the results; With this proposal it is intended to develop the programming and simulation of the torsion testing machine taking into account the real instrumentation of the torsion testing machine.